Long-Term Immunogenicity after One and Two Doses of a Monovalent MF59-Adjuvanted A/H1N1 Influenza Virus Vaccine Coadministered with the Seasonal 2009-2010 Nonadjuvanted Influenza Virus Vaccine in HIV-Infected Children, Adolescents, and Young Adults in a Randomized Controlled Trial - Viganò, Alessandra (American Society for Microbiology, 2011)
Few data are available on the safety and long-term immunogenicity of A/H1N1 pandemic influenza vaccines for HIV-infected pediatric patients. We performed a randomized controlled trial to evaluate the safety and long-term immunogenicity of 1 versus 2 doses of the 2009 monovalent pandemic influenza A/H1N1 MF59-adjuvanted vaccine (PV) coadministered with the seasonal 2009-2010 trivalent nonadjuvanted influenza vaccine (SV) to HIV-infected children, adolescents, and young adults. A total of 66 HIV-infected patients aged 9 to 26 years were randomized to receive one (group 1) or two (group 2) doses of PV coadministered with 1 dose of SV. The main outcome was the seroconversion rate for PV at 1 month. Secondary outcomes were the geometric mean titer ratios and the seroprotection rates at 1 month for all vaccines, seroconversion rates at 1 month for SV, and longitudinal changes of antibody titers (ABTs) at 1, 2, 6, and 12 months for all vaccines. Groups 1 and 2 had similar CD4 counts and HIV RNA levels during the study. The seroconversion rate for PV was 100% at 1 month in both groups. ABTs for PV were high during the first 6 months and declined below seroprotection levels thereafter. Longitudinal changes in ABTs were similar in groups 1 and 2 for both PV and SV. The side effects of vaccination were mild and mostly local. In HIV-infected children, adolescents, and young adults, the immune response triggered by a single dose of PV was similar to that obtained with a double dose and was associated with long-term antibody response.